An Impact Assessment of ESF Training Courses for Unemployed in the Province of Bolzano - Francesco Pastore; Marco Pompili (Institute of Labor Economics (IZA), 2022)
This paper evaluates the impact on employment probabilities of two training programs funded by the European Social Fund in the province of Bolzano, Italy. The programs were addressed to particularly vulnerable groups which were much less skilled and educated than the control group from the public employment agency registers. A large share of the benefit recipients are indeed recent migrants, refugees, and women. By using different matching algorithms, this group was made as similar as possible to the control group, at least in terms of observed characteristics, including the employment status up to two years before entering the programme. We find that the short-term impact of the training programs is negative, highlighting the presence of a lock-in effect. However, from the start of the programs, up to the 13th month, this effect reduced to zero. The effect is particularly sizeable and statistically significant for women, migrants, and the highly educated; age does not seem to matter. However, our findings suggest that the programs were especially significant in empowering women and migrants. By providing them with basic skills, including linguistic and technical professional skills, increased their integration by making them seek jobs more actively.
Keywords: D04; J08; J13; J18; J48; 330; active labour market policies; European Social Fund; training; impact evaluation; matching